Multispanning membrane protein SIDT2 increases knockdown activity of gapmer antisense oligonucleotides - Kohshi Kusumoto; Kiyomi Sasaki; Yasunori Uchida; Ayaka Utsumi; Tokuyuki Yoshida; Satoshi Obika; Takao Inoue; Keiichiro Okuhira (Scientific Reports)
Abstract Recent advances in the clinical development of oligonucleotide therapeutics, such as antisense oligonucleotides (ASOs) and small interfering RNAs, have attracted attention as promising therapeutic modalities for genetic and intractable diseases. These oligonucleotide therapeutics exert their efficacy by binding to target RNAs present within cells; however, the mechanisms underlying their cellular uptake, especially their passage through membranes, remain largely unclear. In the nematode, Caenorhabditis elegans, the multi-pass transmembrane protein, SID-1, is involved in the cellular uptake of double-stranded RNAs. In mammals, SIDT1 and SIDT2 (SID-1 transmembrane family, members 1 and 2, respectively) are homologs of SID-1, yet their functional differences are not fully understood. In this study, we conducted a comparative analysis of the amino acid sequences of mammalian SIDT1 and SIDT2 to identify regions characteristic to each. By inducing SIDT1 or SIDT2 expression in human cell lines, we demonstrated that SIDT2 enhanced the knockdown activity of gapmer ASOs and potentially promoted their endosomal escape into the cytosol. Furthermore, by analyzing chimeric proteins of SIDT2 and SIDT1, we identified a region in SIDT2 that might be crucial for the enhancement of gapmer ASO activity. These findings elucidate the novel role of SIDT2 in the transport mechanism of gapmer ASOs and are expected to contribute to further development of oligonucleotide therapeutics.